2012
DOI: 10.1016/j.jfa.2012.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Strong solutions for stochastic partial differential equations of gradient type

Abstract: Unique existence of analytically strong solutions to stochastic partial differential equations (SPDE) with drift given by the subdifferential of a quasi-convex function and with general multiplicative noise is proven. The proof applies a genuinely new method of weighted Galerkin approximations based on the "distance" defined by the quasi-convex function. Spatial regularization of the initial condition analogous to the deterministic case is obtained. The results yield a unified framework which is applied to sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
56
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 21 publications
5
56
0
Order By: Relevance
“…Applied to driving signals given by independent Brownian motions this implies a new regularity result for the variational stochastic solution X corresponding to (1.2), namely P-a.s. local equicontinuity on O T . This complements the regularity results given in [26], where it is shown that |X| m sgn(X t ) ∈ L 2 ([0, T ] × Ω; H 1 0 (O)) and X ∈ L ∞ ([0, T ]; L m+1 (Ω × O)) if the initial condition is regular enough.…”
supporting
confidence: 86%
“…Applied to driving signals given by independent Brownian motions this implies a new regularity result for the variational stochastic solution X corresponding to (1.2), namely P-a.s. local equicontinuity on O T . This complements the regularity results given in [26], where it is shown that |X| m sgn(X t ) ∈ L 2 ([0, T ] × Ω; H 1 0 (O)) and X ∈ L ∞ ([0, T ]; L m+1 (Ω × O)) if the initial condition is regular enough.…”
supporting
confidence: 86%
“…When applied to the Allen-Cahn equation, see [13,Rem. 4.9], the regularity properties are slightly weaker than the ones in Theorem 2.2.…”
Section: Throughout This Paper We Shall Shorthandmentioning
confidence: 99%
“…The question of existence of a unique (variational) solution to equations of the form (1.1) is well-understood: first results were established in [15,14], for an overview in the above stated generality and further references we refer the reader to [16]. Existence of a strong solution under various assumptions appeared in [3,10] and numerical approximations were studied in [11,12]. In the case of linear operator A which generates a strongly continuous semigroup, more is known concerning regularity and maximal regularity (see e.g.…”
Section: Time Regularitymentioning
confidence: 99%